Influence of sea salt on the interfacial adhesion of bitumen–aggregate systems by molecular dynamics simulation. (20th June 2022) - Long, Zhengwu; Tang, Xianqiong; Ding, Yanhuai; Miljković, Miomir; Khanal, Ashok; Ma, Wenbo; You, Lingyun; Xu, Fu
Graphical abstract: Highlights: Sea salt damaged bitumen's original colloidal structure by disaggregating asphaltenes. Saturates played the major role by most extensively diffusing to the surface of silica. SARA fractions' redistribution was driven by water with ions only acting as catalysts. Number of SARA fractions in model decreased the adhesion energy in all environments. Spatiotemporal distribution of SARA fractions at the interface determined the adhesion. Abstract: This research investigated the influence of sea salt on the adhesion properties of bitumen–aggregate systems by molecular dynamics simulations in order to fundamentally understand the mechanism of damage in the seawater environment. The seawater environment was simulated by high concentrations of chloride, sodium, sulfate, magnesium, and calcium ions in water. Bitumen was represented by 3-, 4-, and 12-component models using the COMPASS force field, while the bitumen–seawater–aggregate interfacial model was discontinued by a vacuum layer of 60 Å in thickness. The results demonstrated that the presence of seawater affected the adhesion by facilitating the molecular migrations of bitumen components and by weakening the agglomeration of asphaltene. Consequently, this gradually damaged the colloidal structure of bitumen in the interfacial zone. Saturates played a dominant role in the adhesion in the seawater environment because they were the most likely to diffuse away from the silica surface. Besides the composition of bitumen, the spatiotemporal distribution of its components in the region of the interface was also identified as extremely important for the interpretation of the intrinsic factors which control the adhesion behaviour of thesesystems.